2014
DOI: 10.1097/md.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Metabolic Arrangement During Olfactory Processing

Abstract: The aim of this article is to investigate the cortical metabolic arrangements in olfactory processing by using 18F fluorodeoxyglucose (FDG) positron emission tomography/computed tomography.Twenty-six normosmic individuals (14 women and 12 men; mean age 46.7 ± 10 years) were exposed to a neutral olfactory condition (NC) and, after 1 month, to a pure olfactory condition (OC) in a relatively ecological environment, that is, outside the scanner. All the subjects were injected with 185–210 megabecquerel of 18F FDG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A comparison of FDG uptake after a bolus injection at rest and during stimulation was performed in 11 normosmic subjects and reported, at rest, mainly increased glucose metabolism in left superior, inferior, middle, medial frontal, orbital gyri, and anterior cingulate cortex. Conversely, during olfactory stimulation PET imaging reported hyperactivation in the cuneus, lingual, and parahippocampal gyri, mainly in the left hemisphere [22, 23].…”
Section: Results In Healthy Controlsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of FDG uptake after a bolus injection at rest and during stimulation was performed in 11 normosmic subjects and reported, at rest, mainly increased glucose metabolism in left superior, inferior, middle, medial frontal, orbital gyri, and anterior cingulate cortex. Conversely, during olfactory stimulation PET imaging reported hyperactivation in the cuneus, lingual, and parahippocampal gyri, mainly in the left hemisphere [22, 23].…”
Section: Results In Healthy Controlsmentioning
confidence: 99%
“…Therefore, authors considered rest as neutral olfactory stimulation in order to avoid olfactory pollution at rest and, after a month, compared to pure olfactory task activation scan. A comparison of FDG uptake after a bolus injection at rest and during stimulation has been performed [22].…”
Section: Task-related Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent report on a single case neuroimaging study with anosmia, due to COVID-19, revealed reduced metabolic activity in the orbitofrontal cortex, suggesting impaired neural function in this region [ 126 ]. It is well-known that the orbitofrontal cortex is responsible not only for the detection of common odors [ 127 ], but also for executive functions and attentional processing [ 128 , 129 , 130 ]. Thus, although future studies should elucidate this issue, the hypothesis might be advanced that, together with the lack of oxygen to the brain due to respiratory symptoms, executive functions and attentional deficits also arise as a consequence of abnormal activity in the orbitofrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…An [ 18 F]-FDG-PET/CT examination was performed in a 27-year-old right-handed woman, who had been earlier diagnosed with COVID-19 by RT-PCR and suffered from isolated anosmia persisting for 6 weeks [ 233 ]. The scan showed pathological hypometabolism of the left orbitofrontal cortex [ 233 , 234 ], a region which receives projections from the primary olfactory cortex [ 235 , 236 ]. Hyposmia and anosmia due to CNS damage of other etiologies have previously been widely investigated by molecular imaging, especially in the context of Parkinson’s disease [ 237 239 ], where anosmia is an early presenting symptom.…”
Section: Chest Imagingmentioning
confidence: 99%